Acute Exercise and Neurocognitive Development in Preadolescents and Young Adults: An ERP Study - Chien-Heng Chu; Arthur F. Kramer; Tai-Fen Song; Chih-Han Wu; Tsung-Min Hung; Yu-Kai Chang (Neural Plasticity)
The purpose of this study was to examine the effect of a single bout of exercise on neurocognitive function in preadolescent children and young adults by determining the modulatory role of age and the neuroelectrical mechanism(s) underlying the association between acute exercise and executive function. Twenty preadolescents and 20 young adults completed the Stroop test, and neuroelectrical activity was recorded during two treatment sessions performed in a counterbalanced order. Exercise treatments involved moderate intensity aerobic exercise for 20 min as the main exercise and two 5 min periods of warm-up and cool-down. The control treatment participants read for a similar duration of time. Acute exercise improved participant reaction times on the Stroop test, regardless of Stroop congruency, and greater beneficial effects were observed in young adults compared to those in preadolescents. The P3 amplitudes increased after acute exercise in preadolescents and young adults, but acute exercise induced lower conflict sustained potential (conflict SP) amplitudes in preadolescent children. Based on these findings, age influences the beneficial effect of acute exercise on cognitive performance in general. Furthermore, the event-related brain potential differences attributed to acute exercise provide a potential clue to the mechanisms that differentiate the effects of acute exercise on individuals from preadolescence to young adulthood.